2020
DOI: 10.1101/2020.06.16.154658
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lack of susceptibility of poultry to SARS-CoV-2 and MERS-CoV

Abstract: word count 48 11 Chickens, turkeys, ducks, quail and geese were challenged with SARS-CoV-2 or MERS-12 CoV. No disease was observed, no virus replication was detected, and antibodies were not 13 detected in serum. Neither virus replicated in embryonating chicken's eggs. Poultry are unlikely 14 to serve a role in the maintenance of either virus. 15 Text-word count 766 16 Coronaviruses (CoV) of animals periodically transmit to humans (1) as recently occurred with 17 SARS-CoV-2. SARS-CoV-2 was first recognized in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 9 publications
1
39
0
1
Order By: Relevance
“…Furthermore, neither IN-inoculated nor cohoused ducks excreted viral RNA in swab samples, and all of the animals were seronegative 14 dpi [ 154 ]. Likewise, chickens, ducks, turkeys, quail and geese challenged with SARS-CoV-2 did not show any clinical signs, and no virus replication or antibodies have been detected [ 155 ]. These experiments suggest that poultry are not susceptible to the virus, and it is unlikely that they play a role in COVID-19.…”
Section: Sars-cov-2mentioning
confidence: 99%
“…Furthermore, neither IN-inoculated nor cohoused ducks excreted viral RNA in swab samples, and all of the animals were seronegative 14 dpi [ 154 ]. Likewise, chickens, ducks, turkeys, quail and geese challenged with SARS-CoV-2 did not show any clinical signs, and no virus replication or antibodies have been detected [ 155 ]. These experiments suggest that poultry are not susceptible to the virus, and it is unlikely that they play a role in COVID-19.…”
Section: Sars-cov-2mentioning
confidence: 99%
“…On the other hand, Ulrich et al (71) reported that cattle had low susceptibility to SARS-CoV-2 infection. While pigs and several poultry species including chickens, turkeys, ducks, geese, and Japanese quail were not susceptible to SARS-CoV-2 infection (30,48,72,73). Furthermore, rabbit and guinea pig housed with COVID-19 patients were tested negative for SARS-CoV-2 infection (74).…”
Section: Other Animalsmentioning
confidence: 99%
“…Experimental infections in dogs (10), cats (10,11), ferrets (10,12), hamsters (13,14), rhesus macaques (15), tree shrew (16), cynomolgus macaques (17), grivets (18), common marmosets (19), rabbits (20), and fruit bats (21) have shown that these species are susceptible to SARS-CoV-2, and experimentally infected cats, tree shrews, hamsters and ferrets could transmit the virus. In contrast, experimental infection of pigs and several poultry species with SARS-CoV-2 proved to be unsuccessful (10,21,22). SARS-CoV-2 has also sporadically been identified in naturally infected animals.…”
Section: Main Textmentioning
confidence: 99%